Análise das dimensões influenciadoras do sucesso em projetos de BI através de data mining - Cordeiro, B.; Alturas, B.; Moro, S. (12th Iberian Conference on Information Systems and Technologies, CISTI 2017, 2017)
Business Intelligence (BI) is an emergent domain with numerous implementation projects proliferating in the industry. However, several factors may influence the success of such projects. This study addresses the identification of the relevant dimensions that may affect success for leveraging a future empirical analysis of BI projects in Portugal through data mining using the quantitative features hereby identified.